Pengembangan Instrumen Tes Matematika TIPE TIMSS Untuk Siswa SMP Konteks Bengkulu - Edi Susanto Susanto; Rusdi Rusdi (Universitas Bengkulu, 2022)
This study aims to develop a TIMSS type of mathematical instrument and improve students' ability to develop evaluation tool. The research conducted is research and development. The development stages consist of: (1) compiling test specifications, (2) writing test questions, (3) reviewing test questions, (4) conducting test trials, (5) analyzing items, (6) improving the test. The research subjects were 32 students of the Mathematics Education Study Program, FKIP Bengkulu University. The test subjects in this study were 24 students of class VIII SMP in Bengkulu City. The results of the research are: (1) TIMSS type SMP mathematics questions in Bengkulu context as many as 15 multiple choice questions and 5 descriptions (2) TIMSS type mathematics questions meet the valid and reliable criteria. (4) there is an increase in students' ability about the instrument from the pretest and posttest with an average increase of 45.25%.